2020
DOI: 10.1007/s00256-020-03398-9
|View full text |Cite|
|
Sign up to set email alerts
|

Flat-panel CT arthrography for cartilage defect detection in the ankle joint: first results in vivo

Abstract: Objectives The purpose of this study was to compare the diagnostic performance of flat-panel computed tomography (FPCT) arthrography for cartilage defect detection in the ankle joint to direct magnetic resonance (MR) arthrography using multidetector computed tomography (MDCT) arthrography as the reference standard. Methods Twenty-seven patients with specific suspicion of articular cartilage lesion underwent ankle arthrography with injection of a mixture of diluted gadolinium and iobitridol and were examined co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Clinically, there are four types of medial malleolus loss, 7,8,[12][13][14][15][16] including medial malleolus soft tissue and partial cortical bone loss (type I), medial malleolus soft tissue and non-weight bearing articular surface loss (type II), medial soft tissue and medial malleolus loss (type III) and distal tibia soft tissue and weight bearing articular surface loss (type IV). Among them, the medial soft tissue and medial malleolus loss (type III) is more complicated with a large number of tissue structure defects, which make surgical repair more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, there are four types of medial malleolus loss, 7,8,[12][13][14][15][16] including medial malleolus soft tissue and partial cortical bone loss (type I), medial malleolus soft tissue and non-weight bearing articular surface loss (type II), medial soft tissue and medial malleolus loss (type III) and distal tibia soft tissue and weight bearing articular surface loss (type IV). Among them, the medial soft tissue and medial malleolus loss (type III) is more complicated with a large number of tissue structure defects, which make surgical repair more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…For high‐resolution imaging of intrinsic wrist structures, FPCT‐A was superior to MR‐A with regard to image quality and time‐efficiency [32]. In a more recent study, Pagliano et al demonstrated FPCT‐A to have better accuracy than 1.5‐T MR‐A in the detection of cartilage defects in the ankle joint [22]. Similarly, Pirimoglu et al reported higher sensitivity, specificity, and accuracy rates for multi detector CT‐A compared with MR‐A with 3D VIBE sequences in the detection and grading of osteochondral lesions [23].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MRI is the most commonly used imaging modality to evaluate OLT [11, 15]. However, improvements in CT technology have renewed interest in CT arthrography [5, 20], and recent studies suggested that flat‐panel computed tomography (FPCT) allows precise evaluation of cartilage thickness and defects [10, 22].…”
Section: Introductionmentioning
confidence: 99%
“…86 In comparison with 1.5 T MRI, CBCT-arthrography has shown superior diagnostic performance in ankle cartilage defect detection in 1 study. 87 Cone-beam CT studies comparing its ability to detect fractures compared with plain radiographs, including those of the wrist, hand, finger, ankle, foot, and toe, demonstrated a remarkable improvement in sensitivity for detecting subtle fractures. 88 There is also an increase in the agreement of the advised orthopedic therapy owing to CBCT interpretation from moderate to near perfect.…”
Section: Trauma and Fracture Imagingmentioning
confidence: 99%
“…In addition, CBCT-arthrography protocols have shown better contrast-to-noise ratios and small structure spatial resolutions, showing potential for tailored protocols for cartilage evaluation 86 . In comparison with 1.5 T MRI, CBCT-arthrography has shown superior diagnostic performance in ankle cartilage defect detection in 1 study 87 …”
Section: Cone-beam Ctmentioning
confidence: 99%